MELEBIHI BATAS MAKSIMUM (Suatu Penelitian di Kabupaten Aceh Selatan). - Zulkarnaini, Suhaimi, M. Gaussyah. (Jurnal Ilmu Hukum, 2015)
Abstract: Article 1 of the Act Number 56, 1960 states that the maximum limit of owning and having agriculture land is 20 Ha/family. This research aims to explore and explain the owning and having of land for agriculture over from its maximum limit in Aceh Selatan District. This is juridical empirical research. The research shows that firstly, the owning and having of the agriculture land is over its maximum limit in Aceh Selatan District as there is no monitoring towards this owning, it is easy for land transaction and there is no Land reform consideration committee. The efforts that have been done by the National Land Authority are by computerizing of land documen integrated online by the land location since 2011 while the land documen from 2011 and before the date cannot be done by this process, planning the establishment of the Land reform committee in the district. The local government should have computerized system of the land online beginning from the transaction in the village, the Sub District Office, PPAT and the National Land Authority Office. The local government should monitor strictly on the land status, its owning of the state land against the procedure. Key words: owning, agriculture, land, over, maximum limit. Abstrak: Pasal 1 UU No. 56 PrpTahun 1960 menegaskan bahwa: Batas maksimum penguasaan tanah pertanian 20 Ha/ KK. Penelitian ini bertujuan, untuk mengetahui dan menjelaskan terjadinya penguasaan tanah pertanian melebihi batas maksimum di Kabupaten Aceh Selatan.Metode penelitian yang digunakan adalah penelitian yuridis empiris. Hasil penelitian menunjukan terjadinya penguasaan tanah pertanian melebihi batas maksimum karena tidak ada pengawasan terhadap penguasaan tanah, mudahnya transaksi jual-beli tanah dan belum terbentuknya Panitia Pertimbangan Landreform. Upaya yang telah dilakukan oleh Kantor Pertanahan melakukan komputerisasi data pertanahan mulai terintergrasi secara online dengan lokasi tanah sejak Tahun 2011 sementara data pertanahan mulai tahun 2011, perencanaan pembentukan Panitia Pertimbangan Landreform Kabupaten. Disarankan kepada Pemerintah perlu adanya system pendataan komputerisasi data pertanahan online mulai dari transaksi jual-beli tanah di tingkat Desa sampai Kantor Pertanahan. Pemerintah Daerah perlu melakukan pengawasan secara ketat terhadap status tanah, pemilikan tanah dan proses penguasaan tanah Negara yang tidak sesuai prosedur Kata Kunci :Penguasaan dan pemilikan tanah pertanian melebihi batas maksimum.